2001
DOI: 10.1128/jcm.39.5.1903-1911.2001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Subgenic 18S Ribosomal DNA PCR and Sequencing for Genus and Genotype Identification of Acanthamoebae from Humans with Keratitis and from Sewage Sludge

Abstract: This study identified subgenic PCR amplimers from 18S rDNA that were (i) highly specific for the genus Acanthamoeba, (ii) obtainable from all known genotypes, and (iii) useful for identification of individual genotypes. A 423-to 551-bp Acanthamoeba-specific amplimer ASA.S1 obtained with primers JDP1 and JDP2 was the most reliable for purposes i and ii. A variable region within this amplimer also identified genotype clusters, but purpose iii was best achieved with sequencing of the genotype-specific amplimer GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
434
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 482 publications
(452 citation statements)
references
References 39 publications
14
434
0
4
Order By: Relevance
“…HRM may therefore provide relevant additional information for the comprehensive classification of protozoa (Ledee et al, 2003;Marciano Cabral, 2003) and confirm hypothesis suggesting that the named taxa based on 18S rDNA Rns phylogenetic relationship genotyping are not monophyletic entities. In previous 18S rDNA-based reports, the genotype T4 was predominant (~85%) (Boggild et al, 2009;Booton et al, 2009;Ledee et al, 2003;Lorenzo-Morales et al, 2010;Schroeder et al, 2001;Zhao et al, 2010). However, in Greece, the genotypes T2, T3, T5, T6, and T11 have been identified (Spanakos et al, 2006) and in Slovakia and the Czech Republic the genotypes T15, T4, and T3 were detected in AK (Nagyová et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…HRM may therefore provide relevant additional information for the comprehensive classification of protozoa (Ledee et al, 2003;Marciano Cabral, 2003) and confirm hypothesis suggesting that the named taxa based on 18S rDNA Rns phylogenetic relationship genotyping are not monophyletic entities. In previous 18S rDNA-based reports, the genotype T4 was predominant (~85%) (Boggild et al, 2009;Booton et al, 2009;Ledee et al, 2003;Lorenzo-Morales et al, 2010;Schroeder et al, 2001;Zhao et al, 2010). However, in Greece, the genotypes T2, T3, T5, T6, and T11 have been identified (Spanakos et al, 2006) and in Slovakia and the Czech Republic the genotypes T15, T4, and T3 were detected in AK (Nagyová et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Great improvement was obtained using TaqMan rtPCR tests but they are unable to detect strains from genotype T5 (Qvarnstrom et al, 2006) and A. astronyxis (Da Rocha-Azevedo et al, 2009;Qvarnstrom et al, 2006). Moreover, the cost for the numerous TaqMan probes and for the postamplification procedures required for characterizing Acanthamoeba is high (Gatti et al, 2010;Goldschmidt et al, 2009b;Khairnar et al, 2011;Rivera and Adao, 2009;Schroeder et al, 2001;Yera et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…25 Extensive studies in the laboratory at Ohio State University and elsewhere have revealed many distinct Acanthamoeba genotypes of nuclear 18S rDNA. 24,[26][27][28] They also have shown, however, that most Acanthamoeba keratitis cases are associated with a single sequence type. 24,26 It is not known whether there is any correlation between sequence types and the pathogenic potential of Balamuthia.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis based on these partial sequences has been proven equally as effective as that of the entire gene in obtaining the information required for the detection of Acanthamoeba as well as for phylogenetic analysis (Schroeder et al 2001). Schroeder et al (2001) also used the PCR product ASA.S1, which was acquired with primers JDP1 and JDP2, specifically for the detection of Acanthamoeba spp. The product is highly genus-selective and can be acquired from all known 18S rDNA genotypes.…”
mentioning
confidence: 99%